Pore structure characterization of shales using synchrotron SAXS and NMR cryoporometry. (April 2019) - Zhao, Yixin; Peng, Lei; Liu, Shimin; Cao, Bao; Sun, Yingfeng; Hou, Bofeng
Abstract: The characterization of shale pore structure is extremely important to shale gas exploitation. Various techniques have been employed to characterize the pore size distribution (PSD) in shales. Small angle X-ray scattering (SAXS) is a relatively new technique that can be applied to obtain the PSD of porous materials. However, little work has been done on shales by synchrotron SAXS. In this paper, scanning electronic microscopy (SEM), nuclear magnetic resonance cryoporometry (NMRC), and synchrotron small-angle X-ray scattering (SAXS) were used to comprehensively characterize pore structure in three shales with a total organic carbon content of 0.68%, 3.68% and 4.3%. The processing and postprocessing for synchrotron SAXS data were executed. Based on background deduction, a positive deviation correction of SAXS data was conducted. SEM was combined with synchrotron SAXS to explore whether the sample is a single dispersion. Two models (Gauss distribution model and the maximum entropy model) for calculating the PSD by synchrotron SAXS were compared with the results by NMRC. The PSD from the Gauss distribution presents good consistency with the PSD from the NMRC with a diameter of less than 15 nm. Notably, a PSD obtained by maximum entropy model and NMRC is more consistent for pores with a diameter of 15–48 nm. Nanopore structure was also explored and discussed based on the Porod theory. Methods for quantitative characterization of pore size proposed in this paper are applicable to other two-phase rock media. Highlights: Pore structure of shales was characterized by using synchrotron SAXS and NMR cryoporometry. A positive deviation correction of SAXS data of shales was conducted. Comparison between SAXS and NMR results obtained from Gauss distribution and the maximum entropy model.